Perlindungan Hukum bagi Konsumen terhadap Pembatalan Transaksi Jual Beli Online menggunakan Metode Paylater - Renaldy Octavianus Tandiono; Heru Saputra Lumban Gaol (Kertha Patrika, 2025)
Paylater is an electronic-based financing service to postpone payments to be repaid at a later date. Paylater can generally be said to be a receivable agreement regulated in Article 1754 of the Civil Code. This service arises due to e-commerce innovation and the development of fintech companies. OJK noted that paylater financing in Indonesia reached 79.92 million in 2023. This paylater financing figure is supported by the increasing use of buying and selling transactions in e-commerce. There is a case where consumers experience losses for using paylater services due to the cancellation of transactions in e-commerce by the marketplace. Problems arise regarding the party that should be responsible in this case because of the complexity of buying and selling transactions in e-commerce which involves the role of various business actors, both marketplaces, merchants, and finance companies. This research aims to examine the legal protection for consumers over the cancellation of buying and selling transactions using the paylater method in the marketplace. The research is a normative juridical research with a statutory and conceptual approach. The results showed that consumers can obtain repressive legal protection in the form of compensation based on Article 19 paragraph (1) of the Consumer Protection Law and Article 10 paragraph (1) of POJK No.22 of 2023 concerning Consumer and Community Protection in the Financial Services Sector.